RANCANG BANGUN WEBSITE DEWAN KERAJINAN NASIONAL (DEKRANAS) DAERAH KOTA BAUBAU SEBAGAI MEDIA INFORMASI DAN PROMOSI SOUVENIR KERAJINAN KHAS BUTON - Hamsinar, Henny; Setiawan H., Teguh; Pasrahmaya, Wa Ode Halmia (Prodi Teknik Informatika Unidayan Baubau, 2018)
National Crafts Council Baubau City (Dekranas) is one of the organizations under the auspices of the Department of Industry and Trade. The Department of Industry and Trade supports the smooth operation of the regional level Dekranas activities that function in assisting and as a government partner in fostering and developing regional handicraft products. The results of handicrafts that are in the Baubau City Dekranas showroom do not have applications that manage data in full such as the name of the goods, the origin of manufacture, craftsman data as well as information for marketing handicraft products. This study aims to design and create a website for the Baubau City Regionalran National Conference as a media for information and promotion of typical Buton craft souvenirs to make it easier to promote and sell the products of typical Balinese handicraft UKM through the Baubau Regional Regionalranean National Conference. The data collection method used is observation and interview with the management of the City of Baubau Dekranas. The results of this study are by utilizing the website created, the Baubau City Decranas can expand the marketing network, promote and sell souvenirs produced by Buton handicrafts produced by UKMs of the Baubau City community so that they can be known by the public both domestically and abroad.Keywords: Dekranas, Souvenirs, Website.